Hubungan Keaktifan Ibu, dan Pengetahuan Pola Asuh Ibu dalam Posyandu Mempengaruhi Status Gizi Balita - Asniah, Fitri Nur (SIMFISIS Jurnal Kebidanan Indonesia, 2024)
Background: The activeness of mothers' visits to posyandu is one of the achievements in fulfilling the nutritional status of toddlers with various incidents of malnutrition such as stunting, wasting and overweight.Objective: To determine the relationship between maternal activity at the posyandu and maternal parenting patterns on the nutritional status of toddlers.Method: The method used in this research is Cross-Sectional. The population in this study were all mothers with toddlers who had a Healthy Way Card (KMS) in Sekarwangi Village in the Sekarwangi Health Center Working Area, who visited the Posyandu as many as 70 people. The sampling technique for this research was simple random sampling of 42 mothers with toddlers. The data collection tools used for maternal activity variables and child nutritional status variables were toddler KMS and maternal activity observation sheets at Posyandu. Data analysis used the chi-square test.Results: The results of this study show a relationship between maternal activity at the posyandu and the nutritional status of toddlers at the posyandu with a p-value <0.05. The relationship between parenting styles and the nutritional status of toddlers at posyandu has a p-value <0.05.Conclusion: There is a relationship between maternal activity at the posyandu and maternal parenting patterns on the nutritional status of toddlers in Sekarwangi Village in the Sekarwangi Community Health Center Working Area.